KONSTRUKSI MAKNA SULUK BAGI IBU BEKERJA JAMA’AH TAREKAT NAQSYABANDIYAH DI DESA TAMBUSAI UTARA KABUPATEN ROKAN HULU - Armayanti, Wita; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Suluk tradition has become a familiar thing in the City of Rokan Hulu Regency. Suluk is a top priority as well as a separate phenomenon for the people of Rokan Hulu Regency. Especially in North Tambusai Village, Suluk has become one of the religious activities favored by the community. Interestingly, those who follow Suluk in North Tambusai Village are not only the elderly but also working mothers, where they not only take care of their household affairs but also help in improving the economy, and they are willing to not work while participating in Suluk. So the purpose of this study was to determine the meaning of Suluk for working mothers of the Naqsyabandiyah Congregation in Tambusai Utara Village, Rokan Hulu Regency.This study uses a qualitative research method with a phenomenological approach. The informants in this study were working mothers who participated in the Suluk Jama'ah Naqsyabandiyah Order, totaling 7 people. Purposively selected. The data collection techniques used are through observation, interviews, and documentation. In achieving the validity of the data in this study, the researchers used data interpretation and data triangulation.The results of this study indicate that the motives of the working mother of the Naqsyabandiyah Congregation in Tambusai Utara Village, Rokan Hulu Regency, are in the form of a motive because of (Because Motive) Tradition, a motive for the background of family problems, a motive for influencing friends, the fourth motive is the motive descendants. While the future motive (In Order To Motive) is to get inner satisfaction, make it easier in all affairs and always remember Allah. The meaning of Suluk for Working Mothers of the Naqsyabandiyah Congregation in Tambusai Utara Village, Rokan Hulu Regency, namely as an effort to get closer to Allah, as an effort to put trust in Allah in escaping the problems faced, and as a reminder of death, the communication experience of working mothers in the Naqsyabandiyah congregation in North Tambusai Village, Rokan Hulu Regency, namely, a pleasant (positive) communication experience, namely a form of acceptance and support from family, coworkers, and the community. And the communication experience is unpleasant (negative). there is a form of response or negative view of the Jamaa'ah from the family, and the community. As well as time constraints due to busy work.